Humanistic Literacy: The Professional Teacher Concept Missed by Students - Agus Mailana; Isma Aulia Zamaakh Syari; Melani; Muhammad Ridho Laia; Retno Ayu Lestari (Yayasan Zia Salsabila, 2023)
Humanist literacy is the ability to understand all aspects related to humanity. The purpose of writing this article is to find out how humanist literacy teaching taught by teachers can be missed by their students. The method used in this research is a qualitative approach with library study data collection methods. Research data sources are taken from various existing sources such as articles and printed books and then processed into new information. By conducting this research, the results were found, namely (1) A professional teacher is the quality of a teacher who can carry out all his duties in accordance with the field he masters, (2) humanist literacy is needed by a student, because with humanist literacy a child will be able to to read the conditions around him.